2013
DOI: 10.1111/dmcn.12222
|View full text |Cite
|
Sign up to set email alerts
|

Stand up and be counted

Abstract: This commentary is on the original article by Rodby-Bousquet et al. on pages 1009-1015 of this issue.Cerebral palsy (CP) arises from a non-progressive brain injury, resulting in life-long physical disability; but owing to the co-occurring musculoskeletal impairments, deterioration in gross motor abilities ensues during the adolescent years. 1 The natural history also involves three in four individuals experiencing chronic pain; one in three experiencing hip displacement; one in ten experiencing scoliosis; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Nevertheless, we identified postural asymmetries also in the youngest children. This is consistent with findings by Fulford and Brown [27] and Porter et al [6] and may indicate that postural asymmetries may originate early in childhood. The results support the need for early postural interventions to monitor range of motion (ROM) and the development of postural asymmetries from an early age, and continuously throughout life [4,27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, we identified postural asymmetries also in the youngest children. This is consistent with findings by Fulford and Brown [27] and Porter et al [6] and may indicate that postural asymmetries may originate early in childhood. The results support the need for early postural interventions to monitor range of motion (ROM) and the development of postural asymmetries from an early age, and continuously throughout life [4,27].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with findings by Fulford and Brown [27] and Porter et al [6] and may indicate that postural asymmetries may originate early in childhood. The results support the need for early postural interventions to monitor range of motion (ROM) and the development of postural asymmetries from an early age, and continuously throughout life [4,27]. The presence of postural asymmetries remains a concern, as previous studies have reported how they most likely result in soft tissue adaption, contractures, further postural deformities [4,7,12,20] and pain [28].…”
Section: Discussionsupporting
confidence: 92%
“…14 Most of these deformities can be prevented via active surveillance and therefore identification of asymmetries and postural deficits should be used to screen for contractures. 59…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Most of these deformities can be prevented via active surveillance and therefore identification of asymmetries and postural deficits should be used to screen for contractures. [5][6][7][8][9] The Posture and Postural Ability Scale (PPAS) 10 is the only clinical assessment tool designed to assess 'quality' and 'quantity' of posture separately, in the four basic body positions: supine, prone, sitting and standing. 'Quality' of posture, relates to the shape of the body, that is, the particular alignment of body segments in relation to each other and to the supporting surface.…”
Section: Introductionmentioning
confidence: 99%